Interleukin 22 mitigates endothelial glycocalyx shedding after lipopolysaccharide injury. Issue 2 (February 2021) - Taghavi, Sharven; Abdullah, Sarah; Duchesne, Juan; Pociask, Derek; Kolls, Jay; Jackson-Weaver, Olan
Abstract : BACKGROUND: The endothelial glycocalyx (EG) on the luminal surface of endothelial cells contributes to the permeability barrier of vessels and prevents activation of the coagulation cascade. Endothelial glycocalyx damage, which occurs in the shock state, results in endotheliopathy. Interleukin (IL)-22 is a cytokine with both proinflammatory and anti-inflammatory properties, and how IL-22 affects the EG has not been studied. We hypothesized that IL-22:Fc, a recombinant fusion protein with human IL-22 and the Fc portion of human immunoglobulin G1 (which extends the protein half-life), would not affect EG shedding in endothelium after injury. METHODS: Human umbilical vein endothelial cells (HUVECs) were exposed to 1 μg/mL lipopolysaccharide (LPS). Lipopolysaccharide-injured cells (n = 284) were compared with HUVECs with LPS injury plus 0.375 μg/mL of IL-22:Fc treatment (n = 293) for 12 hours. These two cohorts were compared with control HUVECs (n = 286) and HUVECs exposed to IL-22:Fc alone (n = 269). Cells were fixed and stained with fluorescein isothiocyanate-labeled wheat germ agglutinin to quantify EG. Total RNA was collected, and select messenger RNAs were quantified by real time - quantitative polymerase chain reaction (RT-qPCR) using SYBR green fluorescence. RESULTS: Exposure of HUVECs to LPS resulted in degradation of the EG compared with control (5.86 vs. 6.09 arbitrary unit [AU], p = 0.01). Interleukin-22:Fc alone also resulted in degradation of EG (5.08 vs. 6.09 AU, p = 0.01). Treatment with IL-22:Fc after LPS injury resulted in less degradation of EG compared with LPS injury alone (5.86 vs. 5.08 AU, p = 0.002). Expression of the IL-22Ra1 receptor was not different for IL-22:Fc treated compared with LPS injury only (0.69 vs. 0.86 relative expression, p = 0.10). Treatment with IL-22:Fc after LPS injury resulted in less matrix metalloproteinase 2 (0.79 vs. 1.70 relative expression, p = 0.005) and matrix metalloproteinase 14 (0.94 vs. 2.04 relative expression, p = 0.02). CONCLUSIONS: Interleukin-22:Fc alone induces EG degradation. However, IL-22:Fc treatment after LPS injury appears to mitigate EG degradation. This protective effect appears to be mediated via reduced expression of metalloproteinases. Abstract : Supplemental digital content is available in the text.